1990
DOI: 10.1148/radiology.174.1.2403680
|View full text |Cite
|
Sign up to set email alerts
|

Short-limb skeletal dysplasias: evaluation of the fetal spine with sonography and radiography.

Abstract: Sonograms and radiographs of the lumbar spine in 51 fetuses and neonates with thanatophoric dwarfism, achondroplasia, and osteogenesis imperfecta type II were retrospectively evaluated. Study data included 27 prenatal and 27 neonatal sonograms and radiographs in 40 fetuses and neonates and 11 cases described in the radiology literature. To precisely compare the sonographic and radiographic appearances of platyspondyly in dysplasia, a simple vertebral ratio was obtained from measurement of vertebral interspace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A severe platyspondyly is typical of TD. Using as indicators the vertebral interspaces (a normalized indicator of the spine length calculated as the sum of the height of one ossified vertebra and the height of an adjacent un-ossified "disk space"), Rouse et al [31] demonstrated a vertebral ratio for TD well below the range of normal spines, but also lower than those of achondroplasic fetuses. From the data of the present study, TD platyspondyly is peculiar because it associates the reduction of the height of the ossified anterior vertebral nucleus with a not-restricted peripheral enlargement in both the antero-posterior and the lateral views.…”
Section: Discussionmentioning
confidence: 99%
“…A severe platyspondyly is typical of TD. Using as indicators the vertebral interspaces (a normalized indicator of the spine length calculated as the sum of the height of one ossified vertebra and the height of an adjacent un-ossified "disk space"), Rouse et al [31] demonstrated a vertebral ratio for TD well below the range of normal spines, but also lower than those of achondroplasic fetuses. From the data of the present study, TD platyspondyly is peculiar because it associates the reduction of the height of the ossified anterior vertebral nucleus with a not-restricted peripheral enlargement in both the antero-posterior and the lateral views.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts are being made to develop a more systematic approach towards these problems by (1) collecting data on normal fetal skeletal anatomy (Rouse et al, 1990;Brons et al, 1990;Goncalves and Jeanty, 1994;Abuhamad et al, 1996); (2) designing special protocols for the prenatal diagnosis work-up (Escobar et al, 1990;Spirt et al, 1990;Avni et al, 1996); (3) clarifying the nomenclature (Spranger, 1988(Spranger, , 1992Horton, 1996); (4) providing data on incidence rates (Rasmussen et al, 1996); and (5) applying the growing amount of molecular data on skeletal dysplasias (Hastbacka et al, 1996;Francomano et al, 1996), which currently allows rapid prenatal molecular confirmation of achondroplasia, and in the future will probably permit the screening of a whole panel of major mutations in different genes that lead to the more common forms of severe skeletal dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The prenatal diagnosis of bone growth disorders has become more common as ultrasound assessments have become more frequent. Nonetheless, the diagnosis of a specific skeletal dysplasia remains challenging (Muller and Cremin, 1985;Weldner et al, 1985;Kurtz et al, 1986;Romero and Sirtori, 1989;Cordone et al, 1993), despite efforts at diagnostic refinement such as the use of femur length-biparietal diameter ratios, vertebral body ratios, or facial profiles (Rouse et al, 1990;Kurtz et al, 1986;Cordone et al, 1993;Turner and Twining, 1993). Likewise, algorithmic approaches to the prenatal diagnosis of various skeletal dysplasias (Escobar et al, 1990;Spirt et al, 1990) most often do not lead to definitive diagnoses.…”
Section: Discussionmentioning
confidence: 99%